(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Eurocode 1998-5 for the design of earth retaining structures in seismic conditions describes calculations using the Mononobe-Okabe method. This simplified quasi-static procedure is to some extent very conservative. The article describes the limits of this method and brings out the comparison using theoretical numerical examples with other approaches. The first, is a calculation method introduced in the American NHCRP 661, the second, is the Chen and Liu method and the last one is the Mylokanis et al. method.